A Comparative Study of Isometric versus Isotonic: Osteoarthrosis Knee: Comparing the Efficacy of Isometric and Isotonic Training for Osteoarthrosis Knee Rehabilitation (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Objectives To investigate the efficacy of Isotonic training in decreasing pain, and increasing balance, walking speed functional mobility in Osteoarthritis Knee.Study design Comparative case control study.Methodology Two hundred (200) individuals with a diagnosis of OA Knee will be selected directly from Physiotherapy outpatient door CMJ University, Department of Physiotherapy, Shillong, Meghalaya. 50 will be qualified for study and are randomly assigned into two groups. Isotonic Exercise group (n = 25) and Isometric Exercise group (n = 25).Results Results indicate that both groups improved in all measures of pain, Balance, and functional outcomes. However, upon Intergroup analysis the mean changes in the score of VAS, WOMAC, TUG will highly significant across the two testing periods (at 6 week 12 week) for the Isotonic training group (FTT) with respect to Isometric training Group (TE).Conclusion Isotonic training on regular basis an effective rehabilitation program for improving functional mobility, balance and decreasing pain in OA Knee.